PENINGKATAN KARAKTER SOPAN SANTUN BERBASIS CIVIC DISPOSITION PADA PESERTA DIDIK KELAS XI MELALUI PEMBELAJARAN PPKN DI SMA NEGERI COLOMADU TAHUN PELAJARAN 2024/2025 - Wardiyanti, Yuanisa; trisiana, anita; Sari, Ama Farida (Prodi PPKn Universitas Slamet Riyadi, 2025)
The purpose of this study is (1) to understand the ways and applications to improve the character of civic disposition-based manners in grade XI students at Colomadu High School, (2) for what are the obstacles when improving the character of civic disposition-based manners in grade XI students through PPKn learning, (3) to find out the efforts to overcome obstacles in improving the character of students' manners. A qualitative research method with a type of case study that determines the views of the subject studied and observed in detail and in depth. The location of this research is at SMA N Colomadu. This research involved the Principal, Vice Principal for Student Affairs, PPKn Teachers, and Students. Interviews, documentation, and observations were used in this study. The study uses source triangulation in checking the validity of the data and triangulation techniques to show the suitability of the research material with the reality in the field. The data analysis technique used is an interactive qualitative descriptive model that begins with data collection, data reduction, data display, and conclusion drawn. The results of the study show that (1) the activities carried out by the school are activities with parents such as routine parenting activities, and students are always given motivation, literacy, and spirituality regarding the importance of civic disposition-based manners. (2) The obstacles faced by students do not understand the importance of politeness and cannot sort out negative things on social media and association. (3) Activities carried out as an improvement in the character of civic disposition-based manners in PPKn learning are by using project-based methods or analyzing case studies to improve students' polite character. They are given direction and guidance so that they have a good relationship and have morals that are in accordance with manners. Keywords: Character of Manners, Civic Disposition, Students, PPKn Learning